The Chemist - Meyer, Stephenie, 1973- (New York : Little, Brown and Company, 2016)
She used to work for the U.S. government, one of the darkest secrets of an agency so clandestine it doesnt even have a name. And when they decided she was a liability, they came without warning, and they killed the only other person she trusted. When her former handler offers her a way out, it is her only chance to erase the giant target on her back. But the information she acquires only makes her situation more dangerous. And now she finds herself falling for a man who can only complicate her likelihood of survival....
Keywords: Women spies -- Fiction; Thrillers (Fiction); Spy fiction